Role of Structural, Metabolic, and Functional MRI in Monitoring Visual System Impairment and Recovery. Issue 6 (2nd October 2020) - Sims, Jeffrey R.; Chen, Anna M.; Sun, Zhe; Deng, Wenyu; Colwell, Nicole A.; Colbert, Max K.; Zhu, Jingyuan; Sainulabdeen, Anoop; Faiq, Muneeb A.; Bang, Ji Won; Chan, Kevin C.
Abstract : The visual system, consisting of the eyes and the visual pathways of the brain, receives and interprets light from the environment so that we can perceive the world around us. A wide variety of disorders can affect human vision, ranging from ocular to neurologic to systemic in nature. While other noninvasive imaging techniques such as optical coherence tomography and ultrasound can image particular sections of the visual system, magnetic resonance imaging (MRI) offers high resolution without depth limitations. MRI also gives superior soft‐tissue contrast throughout the entire pathway compared to computed tomography. By leveraging different imaging sequences, MRI is uniquely capable of unveiling the intricate processes of ocular anatomy, tissue physiology, and neurological function in the human visual system from the microscopic to macroscopic levels. In this review we discuss how structural, metabolic, and functional MRI can be used in the clinical assessment of normal and pathologic states in the anatomic structures of the visual system, including the eyes, optic nerves, optic chiasm, optic tracts, visual brain nuclei, optic radiations, and visual cortical areas. We detail a selection of recent clinical applications of MRI at each position along the visual pathways, including the evaluation of pathology, plasticity, and the potential for restoration, as well as its limitations and key areas of ongoing exploration. Our discussion of the current and future developments in MR ocular and neuroimaging highlights its potential impact on our ability to understand visual function in new detail and to improve our protection and treatment of anatomic structures that are integral to this fundamental sensory system. Level of Evidence 3:   Technical Efficacy Stage 3: